TETRAD EFFECT IN RARE EARTH ELEMENT DISTRIBUTION PATTERNS: A METHOD OF QUANTIFICATION WITH APPLICATION TO ROCK AND MINERAL SAMPLES FROM GRANITE-RELATED RARE METAL DEPOSITS - Monecke T.; Kempe U.; Sala M.; Wolf D.; Monecke J. (My University, 2002)
In some geological environments, the tetrad effect can be observed as a split of rare earth element (REE) patterns into four rounded segments. A new method is proposed to quantify the sizes of the individual segments, and for the first time, the significance of observed tetrad effects is evaluated by taking analytical errors into account. The outlined method was applied to lanthanide patterns of whole-rock and fluorite samples collected from granite-related rare metal deposits. The REE patterns of the granite and greisen samples investigated exhibit significant tetrad effects that may not be accounted for by analytical uncertainties. It is shown that the study of whole-rock samples is insufficient to determine whether this effect is developed during fractional crystallization or is due to other processes such as fluid-rock interaction. A concave tetrad effect mirroring the pattern of the whole-rock samples was not observed in the REE patterns of related vein fluorite samples. Therefore, it is unlikely that the convex tetrad effect in the samples from the magmatic environment can be explained by removal of a respective complementary REE pattern by a coexisting hydrothermal fluid, as previously suggested. It is proposed that the tetrad effect formed within the magma-fluid system before emplacement in the subvolcanic environment where phase separation caused a split of this system into fluid and magma subsystems. Alternatively, the tetrad effect may also be inherited from an external fluid influencing the system during or after the emplacement of the magma. On the basis of the fluorite data, it is shown that the behavior of Eu in the fluids is not related to the tetrad effect. Consequently, different physico-chemical factors control the occurrence of both phenomena. Y was found to be strongly enriched in samples precipitating from hydrothermal fluids that experienced prolonged interaction with the wall-rocks, whereas the tetrad effect in the fluids vanished with time and increasing distance from the ore-bearing granite. Thus, these different geochemical parameters can be used to reconstruct different aspects of the fluid evolution within this type of deposit.